Where is the wealth of nations? : measuring capital for the 21st century. - Hamilton, Kirk, 1951- (World Bank e-Library., 2006)
The book presents estimates of total wealth for nearly 120 countries, using economic theory to decompose the wealth of a nation into its component pieces: produced capital, natural resources and human resources. The wealth estimates provide a unique opportunity to look at economic management from a broader and comprehensive perspective. The book's basic tenet is that economic development can be conceived as a process of portfolio management, so that sustainability becomes an integral part of economic policy making. The rigorous analysis, presented in accessible format, tackles issues such as g.